Cricket bats, #riotcleanup, and rhubarb: Everyday creativity in Twitter interactions around Test Match Special. (January 2018) - Gillen, Julia
Abstract: Changes in society brought about by use of social media have reverberated in public sports discourse giving opportunities for performances of shared culture. I investigate everyday linguistic creativity in the communicative practices of Jonathan Agnew, a commentator for the British Broadcasting Corporation and his networked audiences through Twitter and the radio programme, Test Match Special (TMS). I explore how Agnew and others demonstrated linguistic creativity in situated interactions, transversing physical/digital boundaries that were entwined with specific socio-economic and historical contexts. Through the analysis of two topic clusters, I show how collaboratively constructed shared cultural understandings of the setting and flows across two media channels invoke complex chronotopes. Twitter performances of layered simultaneity are shown to be valued elements of creativity. This study contributes to current sociolinguistic research in expanding understandings of (i) everyday linguistic creativity as strategic performance in specific, complex contexts; (ii) how space and time can be discursively reworked in social media, sometimes presumed to be concerned with the present moment; and (iii) how flexible approaches to ethnography can contribute to such research.